(untitled) (Proceeding Of Sari Mulia University Midwifery National Seminars, 2023)
Background: The data of pregnant women in the working area of ​​Pulang Pisau Health Center in November 2022 is around 115 pregnant women. Pregnant women still experience back pain, especially in the working area of ​​Pulang Pisau Health Center. One way to reduce back pain is by doing pregnancy exercises. Objective: To find out the Regularity of Pregnant Women in the Implementation of Pregnancy Exercise to Overcome Low Back Pain in the Working Area of ​​Pulang Pisau Health Center in 2022. Methods: This research used the pre-experimental design method type one group pretest-posttest. Results: Based on the results of the research, it was shown that there were differences in the average value of the effect of regularity of pregnant women in carrying out pregnancy exercise to reduce low back pain between the pre-test and post-test. The average value of pregnancy exercise during the pre-test was 1.20 with an SD of 0.074. Meanwhile, the average value of pregnancy exercise during the post-test increased by 2.00 with an SD of 0.000 and the average value of low back pain during the pre-test was 1.30 with an SD of 0.085. Meanwhile, the average value of low back pain during the post-test increased by 2.83 with an SD of 0.069. The statistical test found that the significance value of the p value was 0.000 <α (0.05), which means the hypothesis was accepted. Conclusion: Based on the results of the research, it was found that there was a significance value of p <α (0.05) which means the hypothesis was accepted, so it can be concluded that there was a difference between the results of the influence of regularity of pregnant women in carrying out pregnancy exercise to reduce pain between the pre-test and post-test conducted on pregnant women in the working area of ​​ Pulang Pisau Health Center.